The role of stimulation, affection, and parenting patterns in stunting among children aged 24-59 months - Yulianti Wulan Sari; Ali Khomsan; Katrin Roosita (AcTion: Aceh Nutrition Journal, 2025)
Stunting remains a chronic nutritional issue in Indonesia. The prevalence of stunting has decreased from 30,8% in 2018 to 21,5% in 2023; this rate is still above the WHO threshold of less than 20%. Proper stimulation, affection, and parenting patterns influenced optimal growth in terms of height and weight. This study aimed to analyze the association between stimulation, affection, and parenting practices in stunting among children aged 24–59 months. This case-control study was conducted from March to April 2024 at the Made Health Center, Surabaya City, which consists of 50 toddlers, both stunting and non-stunting, selected using purposive sampling. Stimulation patterns were measured using the Home Observation of Measurement and Environment Inventory (HOME), affection patterns using the Child Adult Relational Experimental (CARE), parenting patterns using the parenting feeding style questionnaire, and nutritional status using anthropometric measurements. Data analysis was performed using the chi-squared test. The results showed that the stimulation patterns were significantly correlated with stunting (p=0,000; OR= 5,90). Affection patterns were also significantly correlated with stunting (P =0,000; OR=13,75). Parenting patterns were significantly correlated with stunting (P =0,000; OR=26,35). In conclusion, stimulation, affection, and parenting patterns were significantly correlated with stunting among children aged 24-59 months.